Institute of Metals Division - Dislocation Sources at Inclusions in Zinc (TN) - Victor V. Damiano; Norman Brown (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1964)
ThE present paper proposes a mechanism of dislocation multiplication at internal inclusions or cavities and presents experimental evidence of such sources in zinc. Using an etching technique recently described by Damiano, Tint, and Herman1 to study the three-dimensional aspects of dislocations in bulk zinc crystals, an investigation was made of helically shaped and closed-loop etch patterns found to be associated with inclusions. Crystals containing 0.1 pet Cd and grown from the melt were deformed slightly by bending and then aged at room temperature to precipitate cadmium at the dislocations. The crystals were cleaved along the (0001) plane and then etched with Gilman's2 etch. Crystals were continuously viewed on the (0001) plane while the etching was in progress and numerous helical and closed-loops etch patterns were continuously recorded as shown in the sequences printed directly from the cine film in Fig. l(a) and (6). These etch patterns are not to be confused with the etch patterns previously reported by Damiano and Herman3 which revealed dissolution spirals on the (0001) plane of high-purity zinc crystals. In the present case, precipitates arranged in the form of closed loops or helicies are progressively uncovered by etching after suitable aging of cadmium doped zinc crystals. Viewed with dark-field illumination as shown in Fig. 2, portions of a helical figure and subboundaries were revealed simultaneously. Continuous viewing while the etching was in progress revealed in Fig. 1(b) that the short line segments observed on single photomicrographs were in fact continuous and described a helix which had its terminus at an inclusion. The observations suggested that a dislocation once nucleated at the interface between the inclusion and matrix may act in such a way as to produce ad-